Is there anybody (new) out there? Seven new species of Ligidium (Isopoda, Oniscidea, Ligiidae) from the Southern Appalachians, eastern North America - Ernesto Recuero; Michael S. Caterino (European Journal of Taxonomy)
In this study, we describe seven new species of Ligidium Brandt, 1833 from the Southern Appalachian Mountains based on morphological and molecular data: Ligidium enotahensis sp. nov., L. nantahala sp. nov., L. protuberans sp. nov., L. gadalutsi sp. nov., L. pacolet sp. nov., L. whiteoak sp. nov., and L. schultzi sp. nov. Our findings significantly enhance the known diversity of this genus in the Nearctic, particularly in eastern North America. Morphological diagnoses are primarily based on traits of the male pleopod 2 endopodite, while molecular data, including mitochondrial Cox1 and nuclear 28S and NaK genes, help delimit all newly described species. Together these genes reveal considerable genetic divergence among the new species and from previously described ones. Phylogenetic analyses revealed clear genetic distinctions among the new species, but did not resolve all relationships. Furthermore, we propose elevating three subspecies of Ligidium elrodii (Packard, 1873) to full species status based on consistent morphological differences, Ligidium chatoogaensis Schultz, 1970, L. hancockensis Schultz, 1970, and L. scottensis Schultz, 1970, thereby increasing the total number of Ligidium species to 68. This research underscores the high species diversity in the Southern Appalachians and the importance of integrating morphological and molecular approaches in taxonomy.